2005
DOI: 10.1074/jbc.m507574200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Membrane Targeting of Human Sphingosine Kinase 1

Abstract: Sphingosine 1-phosphate is a bioactive sphingolipid that regulates cell growth and suppresses programmed cell death. The biosynthesis of sphingosine 1-phosphate is catalyzed by sphingosine kinase (SK) but the mechanism by which the subcellular localization and activity of SK is regulated in response to various stimuli is not fully understood. To elucidate the origin and structural determinant of the specific subcellular localization of SK, we performed biophysical and cell studies of human SK1 (hSK1) and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
135
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 47 publications
5
135
1
Order By: Relevance
“…To cite just one example of a peripheral protein, Young et al (68) showed that 50 M W-7 prevents the binding of sphingosine kinase to the plasma membrane and reasonably attributed this effect to W-7 inhibiting Ca 2ϩ /CaM; recent mutation experiments appear to support this interpretation (69). Our results, however, suggest that this effect could equally well be due to W-7 reducing the surface potential of the plasma membrane, particularly because acidic lipids appear to mediate the membrane association of sphingosine kinase (70). An example of an integral membrane protein is the polymeric immunoglobulin receptor, pIgR, which has a 17-residue membrane-proximal cytoplasmic segment, residues 653-670, that binds Ca 2ϩ /CaM with high affinity (71).…”
Section: Discussioncontrasting
confidence: 54%
“…To cite just one example of a peripheral protein, Young et al (68) showed that 50 M W-7 prevents the binding of sphingosine kinase to the plasma membrane and reasonably attributed this effect to W-7 inhibiting Ca 2ϩ /CaM; recent mutation experiments appear to support this interpretation (69). Our results, however, suggest that this effect could equally well be due to W-7 reducing the surface potential of the plasma membrane, particularly because acidic lipids appear to mediate the membrane association of sphingosine kinase (70). An example of an integral membrane protein is the polymeric immunoglobulin receptor, pIgR, which has a 17-residue membrane-proximal cytoplasmic segment, residues 653-670, that binds Ca 2ϩ /CaM with high affinity (71).…”
Section: Discussioncontrasting
confidence: 54%
“…In vitro studies have shown that hSK1 has high affinity for lipid bilayers rich in phosphatidylserine and that conserved Thr 54 and Asn 89 residues in the putative membrane-binding surface of the protein are necessary for membrane binding in vitro and in cells (49). Furthermore phosphorylation of Ser 225 increases the plasma membrane affinity of hSK1.…”
Section: Discussionmentioning
confidence: 99%
“…The ligand for S1P receptors, S1P, is a bioactive sphinoglipid metabolite formed through the action of the sphingosine kinases SK1 and SK2 (48). Previous work has demonstrated that external stimuli, such as phorbol ester-dependent protein kinase C activation, can promote membrane translocation and activation of SK1 (39,49), suggesting that regulated production of S1P might provide a mechanism for transactivating S1P receptors.…”
Section: Igf-1 and Igf-2 Stimulation Leads To Membranementioning
confidence: 99%
“…N-BAR domain proteins primarily interact with the inner leaflet of the plasma membrane that contains PS, PtdIns, and PtdIns(4,5)P 2 as major anionic lipids. Both PS (37,(63)(64)(65)(66)(67) and PtdIns(4,5)P 2 (48,68) have been shown to play critical roles in recruiting cytosolic proteins to the plasma membrane through electrostatic interactions (8,69). In particular, PtdIns(4,5)P 2 can effectively interact with unstructured polybasic motifs even in the presence of excess PS because of its ability to generate an electrostatic field ideal for multidentate interaction with polybasic motifs (48,49) and to facilitate the formation of an amphiphilic secondary structure, typically an ␣-helix (7).…”
Section: Discussionmentioning
confidence: 99%